Effect of Ultra Filtration Rate (UFR) on Blood Sugar in Diabetes Mellitus Patients with Complications of Chronic Rental Failure Undergoing Hemodialysis - Fera Marliana Sari; Siti Aminah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Diabetes Mellitus is a disease that has a very high prevalence every year throughout the world. Data in America, about 38% of end-stage chronic kidney failure is caused by diabetes mellitus. While data in Asia, almost 60% of people with diabetes mellitus have chronic kidney disease. It is estimated that 30 - 40% of people with Diabetes Mellitus Type I and 20 - 30% Diabetes Mellitus Type II will experience complications of Chronic Kidney Disease. Currently, it is estimated that 25% of patients with chronic renal failure undergoing hemodialysis are caused by type II diabetes mellitus Objective : Knowing the effect of UFR on blood sugar in diabetes mellitus patients with complications of chronic kidney failure undergoing hemodialysis. Methods: Quasi-experimental with a pre-experimental one group pretest-posttest design. The sample in this study were all DM patients with CKD complications undergoing hemodialysis in the Jakarta Hajj Hospital Hemodialysis Room in November 2022 as many as 64 people, the sampling technique was total sampling. Results: Most of the respondents were female 51.6%, aged ≥ 50 years 78.1%, and the standard UFR rate was 68.8%. The average difference in blood sugar levels before and after hemodialysis was 188.7 mg/dl. There is an effect of UFR hemodialysis on blood sugar in diabetes mellitus patients with complications of chronic kidney failure undergoing hemodialysis (p.value 0.000). Conclusions: There is an effect of UFR hemodialysis on blood sugar in diabetes mellitus patients with complications of chronic kidney failure undergoing hemodialysis. Need to improve the quality of independent nursing care in patients with chronic kidney disease undergoing hemodialysis.